Therapeutic Communication Between Therapist and Fracture Patient at Padepokan Padjadjaran Cimande (Komunika, 2024)
This study aims to determine therapeutic communication between therapists and fracture patients at Padepokan Padjadjaran Cimande. The method used in this research is a descriptive qualitative approach with a constructivist paradigm. The theory used in this research is communication accommodation theory. This theory is used to find out how therapeutic communication is carried out by therapists with fracture patients by combining medical and traditional elements. The data collection techniques used were direct observation, in-depth interviews, documentation and literature study. The results of this research show that therapeutic communication has been implemented by the hermitage and has become a way of communicating and educating patients in the treatment of fractures.